Surface Modified Solid Lipid Nanoparticles for Brain Cancer Treatment - Soni, Vandana (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Primary brain tumors are the tumors that grow within the brain from the brain cells. The treatment of primary brain tumor is the biggest challenge in the field of oncology due to the presence of bloodâ€“brain barrier (BBB). The BBB prevents the entry of most of the drugs inside brain cells from the blood. Therefore, the present work was intended to develop and investigate the ability of polysorbate 80 coated solid lipid nanoparticles (SLN) to deliver doxorubicin (DOX) in the brain for the treatment of brain cancer cells. Materials and Methods: The polysorbate 80 coated, DOX loaded-SLN (DOX-SLN) were prepared by the solvent evaporation method using a mixture of tristearin, hydrogenated soy phosphatidylcholine, and cholesterol lipids. DOX-SLN were characterized for various attributes such as average particle size, size distribution, zeta potential, surface morphology, entrapment efficiency, drug release, cytotoxicity, and cellular uptake studies. Cytotoxicity and cellular uptake studies were performed on U87MG brain cancer cell lines. Results and Discussion: DOX-SLN prepared by solvent evaporation method possesses an average particle size near 200 nm and polydispersity index (PDI) below 0.3. The zeta potential of the prepared nanoparticles was found to be -14 mV with 45.3 Â± 0.2% entrapment efficiency. The cytotoxicity studies showed the higher toxicity of DOX-SLN than plain DOX on U87MG cell lines. The cellular uptake studies also confirmed the internalization of the DOX-SLN inside brain cancer cells. Conclusions: The results confirmed the development of a potential carrier for brain cancer treatment with enhanced ability to cross the BBB.